PENDAPATAN USAHATANI KEDELAI DI DESA SUKASIRNA KECAMATAN SUKALUYU KABUPATEN CIANJUR - Nastiti Winahyu; Rita Nurmalina (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2015)
Soybean is one of important food crops in Indonesia after rice and corn. The necessity of dried soybean in the country has not been able to sufficient the demand, so the old pods cultivation and productivity still need to be enhanced. The purpose of this research are to examine the variability, analyze farm income, as well as to analyze the ratio between revenue and cost (R/C) of the old and young pod soybean in Sukasirna Village, Sukaluyu District, Cianjur Regency. The analysis of this research are descriptive and quantitative analysis, namely income analysis and R/C ratio. Farm income over the total cost of old pod soybean is positive and beneficial for cultivated. While the loss occurs in young pod soybean shown with revenue over total costs is negative. Based on the analysis of R/C is known that the benefits derived from old pod soybean larger than the young pod. Results of t-test shows that t count against the total income does not differ significantly between old pod soybean and young pod soybean. This study shows that the farmer prefer to do old pod soybean farming than young pod soybean.